Hydrogen treated anatase TiO2: a new experimental approach and further insights from theory. Issue 7 (1st February 2016) - Mehta, Manan; Kodan, Nisha; Kumar, Sandeeep; Kaushal, Akshey; Mayrhofer, Leonhard; Walter, Michael; Moseler, Michael; Dey, Avishek; Krishnamurthy, Satheesh; Basu, Suddhasatwa; Singh, Aadesh P.
Abstract : Vacuum hydrogen annealing of TiO2 leads to increased visible light absorption. The origin thereof was revealed by ab initio calculations and X-ray photoelectron spectroscopy. Abstract : Hydrogenated TiO2 (H:TiO2 ) is intensively investigated due to its improvement in solar absorption, but there are major issues related to its structural, optical and electronic properties and therefore an easily compatible method of preparation is much needed. In order to clarify this issue we studied TiO2 nanocrystals under the partial pressure of hydrogen to modify the structural, optical and electrical properties and to significantly improve the photocatalytic and photoelectrochemical performance. The hydrogen treated TiO2 nanocrystals contained paramagnetic Ti 3+ centers and exhibited a higher visible light absorption cross-section as was confirmed by electron paramagnetic resonance diffuse reflectance spectra measurements and X-ray photoelectron spectroscopy. The hydrogen annealed samples showed a noticeable improvement in photocatalytic activity under visible light ( λ > 380 nm) which was demonstrated by the degradation of methylene blue dye and an improved photoelectrochemical response in terms of high photocurrent density. Ab initio simulations of TiO2 were performed in order to elucidate the conditions under which localized Ti 3+ centres rather than delocalized shallow donor states are created upon the reduction of TiO2 . Randomly distributed oxygen vacancies lead to localized deep donor states while the occupation of the oxygen vacancies by atomic hydrogen favours the delocalized shallow donor solution. Furthermore, it was found that localization is stabilized at high defect concentrations and destabilized under external pressures. In those cases where localized Ti 3+ states are present, the DFT simulations showed a considerable enhancement of the visible light absorption as well as a pronounced broadening of the localized Ti 3+ energy levels with increasing defect concentration.